Enhancing sustainable agri-food systems using multi-nutrient fertilizers in Kenyan smallholder farming systems - Adolwa, Ivan S.; Mutegi, James; Muthamia, Joses; Gitonga, Angela; Njoroge, Samuel M.; Kiwia, Abednego; Manoti, Dismas; Mairura, Franklin S.; Nchanji, Eileen Bogweh (Elsevier, 2023)
Persistent food insecurity in the global south has triggered calls for sustainable development worldwide. Moreover, more than a quarter of the world's population suffers from micronutrient deficiencies or hidden hunger. The population bulge, declining soil fertility and inadequate/inappropriate use of farm inputs in Sub-Saharan Africa place it in a precarious position. Multi-nutrient fertilizer blends have been mooted as a key innovation in closing yield gaps and boosting food and nutrition security. This study assessed the extent of multi-nutrient fertilizer blends utilization and yield response across agroecological zones and their on-farm profitability under Kenyan smallholder farmer conditions. We collected data through a detailed household survey conducted in eight counties in Kenya representative of high, medium, and low productivity zones using a sample of 1094 smallholder farmers. Multi-nutrient fertilizers increased maize yields significantly (P < 0.05), eliciting a 400% yield increase compared to the control and 108% greater maize yield than conventional fertilizers in the high potential zone. Conversely, at 3.7 t/ha conventional fertilizers elicited a significant (P < 0.05) yield response in Irish potatoes in the high potential areas. Multi-nutrient fertilizers increased on-farm profitability of crops, specifically for potato production systems where a benefit: cost ratio (BCR) of more than 2 was observed. Farmers may break even when they use multi-nutrient fertilizers on maize particularly in the low potential areas. Therefore, there is considerable potential for multi-nutrient fertilizers to increase crop productivity while being economically viable across agroecological zones and cropping systems. However, the uptake of multi-nutrient fertilizers among farmers is quite low across the country, except for small pockets where limited interventions have been carried out. This calls for sustained efforts to scale multi-nutrient fertilizers with a focus on clear messaging that stresses the need to apply appropriate rates of various nutrients including the secondary nutrients and micro-nutrients.